2019
DOI: 10.1101/759159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha Activity Reflects the Magnitude of an Individual Bias in Human Perception

Abstract: Biases in sensory perception can arise from both experimental manipulations and personal traitlike features. These idiosyncratic biases and their neural underpinnings are often overlooked in studies on the physiology underlying perception. A potential candidate mechanism mediating such idiosyncratic biases is spontaneous alpha activity, a prominent brain rhythm known to influence the processing of upcoming information in general. Using a time perception task, we here tested the hypothesis that alpha power refl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 96 publications
(103 reference statements)
3
18
3
Order By: Relevance
“…We removed ICA components that reflect eye movement artefacts, localized muscle activity or poor electrode contacts (17.2 ± 4.45 rejected components per participant, mean ± SD). These were identified as in our previous studies (Grabot & Kayser, 2020;Kayser et al, 2017) following definitions provided in the literature (Hipp & Siegel, 2013;O'Beirne & Patuzzi, 1999). Additionally, trials with amplitude exceeding 175 mV were rejected.…”
Section: Eeg Acquisition and Preprocessingmentioning
confidence: 99%
“…We removed ICA components that reflect eye movement artefacts, localized muscle activity or poor electrode contacts (17.2 ± 4.45 rejected components per participant, mean ± SD). These were identified as in our previous studies (Grabot & Kayser, 2020;Kayser et al, 2017) following definitions provided in the literature (Hipp & Siegel, 2013;O'Beirne & Patuzzi, 1999). Additionally, trials with amplitude exceeding 175 mV were rejected.…”
Section: Eeg Acquisition and Preprocessingmentioning
confidence: 99%
“…Based on the assumption that postdiction is driven by prior expectations, and on previous literature indicating that the influence of priors on perception is reflected in low-frequency oscillatory activity (Sherman, Kanai, Seth, & VanRullen, 2016; Mayer, Schwiedrzik, Wibral, Singer, & Melloni, 2016; Samaha, Boutonnet, Postle, & Lupyan, 2018; Nuttida Rungratsameetaweemana & Serences, 2018), we hypothesized that perceptual reports during the rabbit illusion are similarly related to pre-stimulus oscillatory activity. We thus investigated pre-stimulus alpha activity through the prism of a recent line of research which has suggested a specific interpretation of the role of alpha band oscillations during perceptual decisions: alpha may reflect the influence of idiosyncratic biases on perception (Grabot & Kayser, 2019; Grabot, Kösem, Azizi, & Wassenhove, 2017) and may relate to the decision criterion rather than accuracy (Limbach & Corballis, 2016; Iemi, Chaumon, Crouzet, & Busch, 2017; Samaha, Iemi, & Postle, 2017; Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017; Iemi & Busch, 2018). We found that pre-stimulus alpha power fluctuations in parietal and frontal areas reflect the tendency of an individual to perceive the illusion.…”
Section: Discussionmentioning
confidence: 99%
“…The regions found to be activated in the inward condition, fall within the motor and premotor cortex, known to play a central role in timing perception, especially in the momentarily indexing of ongoing time (Macar, Coull, & Vidal, 2006; Coull, Meck, & Cheng, 2011). Pre-stimulus alpha activity correlating with individual biases was also located in frontal areas, possibly related to cognitive control (Grabot & Kayser, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies propose that alpha brain oscillations may reflect the temporal sequence coordination of the associated neuronal representations. The underlying rhythmic neuronal oscillations operate as an attentional 'gatekeeper' that allocates priority to certain stimuli for WM storage by enabling an optimal signal-to-noise ratio; in this way, possible interference with conflicting sensory inputs (Freunberger et al, 2011;Grabot and Kayser, 2020;Jensen et al, 2014) is avoided or reduced. In this framework, a considerable body of evidence has highlighted a relationship between the alpha phase and timing in perception.…”
Section: Introductionmentioning
confidence: 99%